1987
DOI: 10.1007/bf00296998
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the role of insulin dimerisation and negative cooperativity using the biological properties of the despentapeptide and deshexapeptide insulins

Abstract: Summary. The C-terminus of the insulin B chain is essential for dimerisation and expression of negative cooperativity. In order to evaluate the possible physiological role of these phenomena, we have studied the properties in vivo and in vitro of despentapeptide insulin (B26-30 deleted), derived from beef insulin, and deshexapeptide insulin (B25-30 deleted), derived from pork insulin. These materials do not dimerise and have 15% and 0% retention of negative cooperativity respectively. Lipogenesis potencies in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Previous data from CD-spectroscopy and gel filtration studies suggested that the des-(B26-B30)-insulinamide is essentially monomeric [5]. Thus, the current data support a recent conclusion derived from in vitro and in vivo studies with the non-amidated despenta-and deshexa analogues about the minor physiological importance of dimerisation [17]. The present investigation of analogues with substitutions of the amidated B25 residue by tyrosine or histidine did show insulin-like binding characteristics in rat hepatocytes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous data from CD-spectroscopy and gel filtration studies suggested that the des-(B26-B30)-insulinamide is essentially monomeric [5]. Thus, the current data support a recent conclusion derived from in vitro and in vivo studies with the non-amidated despenta-and deshexa analogues about the minor physiological importance of dimerisation [17]. The present investigation of analogues with substitutions of the amidated B25 residue by tyrosine or histidine did show insulin-like binding characteristics in rat hepatocytes.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, the apparent hepatocyte binding and metabolic potency were indistinguishable. Compared to the non-amidated derivative des-(B26-B30)-insulin, for which a biological potency of approximately 20% was reported when evaluated in rat adipocytes in vitro [4,17], the neutralization of the charged B25 C-terminal carboxylate resulted in a shortened molecule which contained structural and dynamic properties sufficient to elicit full biological potency. These data may contribute to the understanding of the physiological role of dimerisation and negative cooperativity observed for insulin but not the B-chain C-terminal-truncated analogues [18].…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of the five C-terminal residues of the B chain (residues B26-B30) prevents classical dimerization but is otherwise structurally well tolerated in the monomer(118,119). The analogue is a complete agonist in vivo(120) and on amidation of the B25 C-terminus exhibits native receptor binding affinity(58,59).5012 Biochemistry, Vol.44, No. 13, 2005 Wan et al…”
mentioning
confidence: 99%
“…Di-arginyl insulins have a different iso-electric point to that of native insulin as used for recrystallization from 1923, being acid soluble but precipitating in SC tissue at pH 7.4 after injection [25]. It had been known since the 1970-1980s that the insulin B-chain terminal amino acids had no role in insulin action [26], so the concept was that adding two arginine residues would not interfere with receptor binding to any clinically significant extent. However they did increase IGF-1 receptor binding [27].…”
Section: -Todaymentioning
confidence: 99%